Decomposing the Grey Economy in Bulgaria: A General-Equilibrium Analysis - VASILEV, Aleksander (Journal of Mathematical Economics and Finance; Vol 8 No 2 (2022): JMEF, Volume VIII, Issue 2(15), Winter 2022, 2022)
This paper attempts to assess the size of the grey economy, and provide a decomposition by evasion type. The modelling approach utilizes a standard micro- founded general-equilibrium setup, which is augmented with a revenue-extraction mech- anism and a government sector. The model is calibrated to Bulgaria after the intro- duction of the currency board (1999-2018). A computational experiment performed within this setup estimates that on average, the size of total evasion is a bit more than one-fourth of output, an estimate which is in line with the figures provided in both Philip (2014) and the European Commission (2014). Two-thirds of the model- predicted evasion is a combined result of income- and social security evasion, while the rest is due to VAT evasion.